Obuchayushchaya mul'timediya-sistema po vostochnym edinoborstvam (na primere karate-do) - Petrov, P. K.; Dmitriyev, O. B.; Shirokov, V. A. (Teorija i Praktika fiziceskoj Kul'tury, 1998)
The paper is devoted to the description of the Inquiry-Informational Multimedia system on the east single combats of the multifunctional purpose: inquiring, training, controlling. The creation and use of the multifunctional programme complexes is the rational direction for the increase of the effectiveness in the process of teaching and training of specialist in the certain subjects branches.